The Effect of Augmented Reality on Vocabulary Mastery of Seventh Grade Students - Sri Sutanti; Sriati Usman; Mashuri; Nur Sehang Thamrin (LPPM Universitas Advent Indonesia, 2026)
This research aims to investigate the effect of Augmented Reality (AR) on students’ vocabulary mastery among seventh-grade students at SMP Negeri 19 Palu. Vocabulary is a fundamental aspect of language learning, yet many students struggle to master it due to lack of motivation and conventional teaching methods. To address this problem, the researcher applied AR-based learning using the Assemble Edu application, which provides 3D visuals and interactive features to improve engagement. This study used a quasi-experimental method with two groups: an experimental class that received AR-based instruction and a control class that received traditional instruction. Both classes were given a pre-test and post-test to measure vocabulary mastery. The results showed a significant improvement in the experimental class, with an average post-test score of 82.00, compared to 59.80 in the pre-test. Meanwhile, the control class only increased from 63.00 to 72.40. Statistical analysis using SPSS showed that the difference between the two groups was significant (Sig. 2-tailed = 0.001), indicating that AR had a strong positive effect on vocabulary acquisition. These findings support previous research showing that AR enhances motivation, memory retention, and contextual understanding in language learning. The use of AR aligns with constructivist learning theory and supports the Merdeka Curriculum, which emphasizes student-centered and technology-integrated learning. In conclusion, AR-based learning can effectively improve students’ vocabulary mastery and is recommended as a modern instructional strategy in English language teaching